PENERAPAN KONSEP OPEN SPACE TERHADAP PRODUKTIVITAS PADA KANTOR PLAZA BANK MANDIRI SUDIRMAN - Darryl Hendry Aristo; Ade Syoufa; Amira Wati (Jurnal Ilmiah Teknik, 2025)
Open space is a space that arises because of the need to provide a place for humans to meet and communicate. Open space is the concept of an open workspace without partitions. The main feature of the concept of open space is the absence of chambers and partitions. The interior is modern, with modern amenities that cater to the needs of employees, and common spaces. In addition, there are other elements that support the use of open offices to increase productivity, such as light, air, color, and sound. A good office layout and comfort will affect the work productivity of your company's employees.In this study, the author discusses the application of the open space concept to productivity in the Plaza Bank Mandiri Sudirman office building.The research approach was carried out using a qualitative approach that was arranged narratively. Data collection for this study was conducted through interviews and direct observation in the Bank Plaza Mandiri office building. Use secondary data independently, such as through the internet and journals. Find out how open office design impacts employee productivity at Bank Mandiri Sudirman Plaza Office.